OPTIMALISASI PERMAINAN CONGKLAK UNTUK MENINGKATKAN KEMAMPUAN MATEMATIS ANAK USIA DINI DI KB DARUL ULUM BLUMBUNGAN LARANGAN PAMEKASAN - Aminatul Muballighah; Desi Ismawati (Universitas Muhammadiyah Metro, 2026)
Early childhood mathematical abilities need to be developed through engaging learning activities that are appropriate to their learning characteristics. Initial observations at the Darul Ulum Blumbungan Larangan Kindergarten in Pamekasan indicate that some children still experience difficulties in recognizing number symbols and counting because the learning process is still conventional. One effort that can be done is through the traditional game of congklak. This study aims to describe the use of congklak games in improving children's mathematical abilities at the Darul Ulum Kindergarten. This study uses a qualitative descriptive approach. Data collection techniques were carried out through interviews, observation, and documentation. Data analysis used the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions. The results show that congklak games can stimulate children's mathematical abilities, especially in recognizing number symbols, counting number sequences, matching the number of objects with number symbols, and counting the number of objects accurately. The use of congklak as a concrete medium helps children understand the concept of numbers through a fun learning experience and increases children's engagement during the learning process. Thus, the traditional game of congklak can be used as a learning medium that supports the development of early childhood mathematical abilities.